2014
DOI: 10.1016/j.pnpbp.2013.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Impaired empathic abilities and reduced white matter integrity in schizophrenia

Abstract: Empathic abilities are impaired in schizophrenia. Although the pathology of schizophrenia is thought to involve disrupted white matter integrity, the relationship between empathic disabilities and altered white matter in the disorder remains unclear. The present study tested associations between empathic disabilities and white matter integrity in order to investigate the neural basis of impaired empathy in schizophrenia. Sixty-nine patients with schizophrenia and 69 age-, gender-, handedness-, education- and I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 43 publications
2
50
0
Order By: Relevance
“…More recent studies that use tract-based spatial statistics (Smith et al, 2006) reveal a similar pattern (Clemm von Hohenberg et al, 2013; Douaud et al, 2007; Freitag et al, 2013; Fujino et al, 2014; Guo et al, 2012; Holleran et al, 2013; Jeong et al, 2009; Karlsgodt et al, 2009; Karlsgodt et al, 2008; Lee et al, 2013; Liu et al, 2013). Of note, none of the aforementioned studies corrected the FA measure for free-water contamination, and it is likely that such correction would decrease the extent of lower FA values, as demonstrated by Pasternak et al (Pasternak et al, 2012).…”
Section: Discussionmentioning
confidence: 85%
“…More recent studies that use tract-based spatial statistics (Smith et al, 2006) reveal a similar pattern (Clemm von Hohenberg et al, 2013; Douaud et al, 2007; Freitag et al, 2013; Fujino et al, 2014; Guo et al, 2012; Holleran et al, 2013; Jeong et al, 2009; Karlsgodt et al, 2009; Karlsgodt et al, 2008; Lee et al, 2013; Liu et al, 2013). Of note, none of the aforementioned studies corrected the FA measure for free-water contamination, and it is likely that such correction would decrease the extent of lower FA values, as demonstrated by Pasternak et al (Pasternak et al, 2012).…”
Section: Discussionmentioning
confidence: 85%
“…Several studies have found an association between affective or overall empathy and negative symptoms (Bora et al, 2008;Kucharska-Pietura et al, 2012;Lincoln et al, 2011;Shamay-Tsoory et al, 2007;Smith et al, 2014;Sparks et al, 2010); associations have also been found with positive symptoms (Konstantakopoulos et al, 2014;Lysaker et al, 2013;Smith et al, 2014;Sparks et al, 2010), depression (Abramowitz et al, 2014;Didehbani et al, 2012;Horan et al, 2015), anxiety (Achim et al, 2011), and insight (Didehbani et al, 2012;Lysaker et al, 2013;Pijnenborg et al, 2013). However, though several studies report significant relationships with symptoms, as many studies have reported no association (Corbera et al, 2013;Derntl et al, 2012a;Derntl et al, 2012b;Fresán et al, 2015;Fujino et al, 2014;Fujiwara et al, 2008;Lam et al, 2014;Lehmann et al, 2014;McCormick et al, 2012;Montag et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Decreased FA in the left IFOF predicts worse neurocognitive performance both in never-medicated chronic schizophrenia [46] and in adolescents with earlyonset schizophrenia [47] , as well as predicting empathic impairments in patients with schizophrenia [48] . Other whitematter fiber tracts related to the PFC in schizophrenia include the anterior limb of the internal capsule, the medial portion of which includes the anterior thalamic radiation linking the thalamus and the PFC [49,50] , the genu of the corpus callosum linking the bilateral PFCs [51,52] , and deep white matter within the PFC [53] .…”
Section: Arcuate Fasciculusmentioning
confidence: 99%